2002
DOI: 10.1016/s0006-3495(02)75666-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heavy Water on Protein Flexibility

Abstract: The effects of heavy water (D(2)O) on internal dynamics of proteins were assessed by both the intrinsic phosphorescence lifetime of deeply buried Trp residues, which reports on the local structure about the triplet probe, and the bimolecular acrylamide phosphorescence quenching rate constant that is a measure of the average acrylamide diffusion coefficient through the macromolecule. The results obtained with several protein systems (ribonuclease T1, superoxide dismutase, beta-lactoglobulin, liver alcohol dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
168
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(191 citation statements)
references
References 34 publications
22
168
1
Order By: Relevance
“…To answer this, we assigned and measured 15 N and 13 C α chemical shifts 18 as well as 3 J HNHA scalar couplings in the E-mutant and compared them to those of wt tau. Both proteins showed only small deviations from random coil values of 13 C α chemical shifts, in agreement with their disordered nature ( Figure S15). Direct comparison of the experimental 13 C α chemical shifts for wt and E-mutant tau demonstrated that local conformational changes induced by pseudophosphorylation are small and restricted to the vicinity of the mutation.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…To answer this, we assigned and measured 15 N and 13 C α chemical shifts 18 as well as 3 J HNHA scalar couplings in the E-mutant and compared them to those of wt tau. Both proteins showed only small deviations from random coil values of 13 C α chemical shifts, in agreement with their disordered nature ( Figure S15). Direct comparison of the experimental 13 C α chemical shifts for wt and E-mutant tau demonstrated that local conformational changes induced by pseudophosphorylation are small and restricted to the vicinity of the mutation.…”
supporting
confidence: 60%
“…Rigid secondary structure is not induced, in agreement with 3 J HNHA scalar couplings ( Figure S15) and previous work on short tau peptides. 19 Despite the fact that the PHF1 epitope near the C-terminus contains only two phosphorylation sites (396 and 404), 13 C α chemical shift changes were more pronounced and affected a larger set of residues than did glutamic acid mutations in the proline-rich regions, suggesting that the PHF1 epitope is more prone to conformational changes.…”
mentioning
confidence: 99%
“…Generally for smaller proteins, assuming the EX2 mechanism (see "Results"), the highest ⌬G HX value estimated by H/D exchange corresponds to the overall ⌬G U value calculated from the unfolding transition curve obtained with denaturants or with heat (39 -42). On the other hand, there are some possible contributions to the increase in the ⌬G HX value, such as the existence of superprotected residues (43), the effects of solvent isotopes (by Ϯ0 -2 kcal/mol), and proline isomerization (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…(1) Some proteins have been shown to be more stable in 2 H 2 O than in H 2 O, [36][37][38] and the CD data (on which the Ising fits were based) were performed in H 2 O, whereas the HX experiments were performed in 2 H 2 O, but for both CTPR2 and CTPR3 we saw no appreciable difference in protein stability in H 2 O versus 2 H 2 O (Fig. 4a, inset).…”
Section: Native State Hydrogen Exchange (Nhx)mentioning
confidence: 95%